Existence of periodic solutions to fractional p(z)-Laplacian parabolic problems - ZINEDDAINE, Ghizlane; KASSIDI, Abderrazak; MELLIANI, Said (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
We consider a class of nonlinear parabolic initial boundary value problems having the fractional p(z)-Laplacian operator. By combining variable exponent fractional Sobolev spaces with topological degree theory, we establish the existence of a time-periodic non-trivial weak solution. Mathematics Subject Classification (2010): 35B10, 35K55, 47H11, 35R11. Received 02 January 2024; Accepted 20 March 2024.